Shorea macrophylla (Engkabang) Endosperm Extract Elevates Lipogenesis and Adipogenesis in 3T3-L1 Mouse Adipocyte Cells - Hung Hui, Chung; Ivy Chew, Yee Yen; Melinda Lau, Mei Lin; Siong Fong, Sim (The Malaysian Society of Applied Biology, 2025)
The Shorea macrophylla endosperm, also known as illipe nuts, has a high lipid content, making it a favoured dietary choice for wild animals. Its composition is an interesting aspect to investigate, as it is still unknown to date despite its superior high-quality lipid profile. In this research, we conducted endosperm extraction using various solvents to investigate potential lipogenesis-inducing compounds. The acetone showed the highest endosperm extraction efficiency at 38.30% while other solvents achieved efficiency above 30%, except for ethanol and methanol. GCMS analysis revealed common compounds across extracts, with methyl stearate and methyl elaidate being among the most prevalent, except in acetone extraction. Molecular docking experiments demonstrated good binding scores between these compounds and lipogenesis-related proteins, particularly highlighting methyl elaidate's potential. In vitro studies conducted on 3T3-L1 cells confirmed an increase in triglyceride levels with methanol and diethyl ether extracts. Both experimental and computational analyses strengthen the potential of methyl elaidate as a pivotal lipogenesis inducer, with potential implications for enhancing fat storage in meat quality when incorporated into vertebrate diets. The effective lipogenesis-inducing elements mentioned can then be incorporated in the diet of livestock with the hope of increasing the amount of fat stored in meat and improving its overall quality.